DESAIN PERANGKAT LUNAK DAN PEMODELAN SISTEM IRADIATOR SERBAGUNA - Ahmad Rifai; M. Ikhsan Shobary; Gunarwan Prayitno (Jurnal Perangkat Nuklir, 2010)
SOFTWARE DESIGN AND MODELLING OF A MUL T/PURPOSE IRRADIA TOR SYSTEM. Software design and simulation model for a multi-purpose irradiator has been done. The studied irradiator consits of 19 carriers which move along a defined irradiation path where 9 stoppers are also located. These stoppers are used to control the movement of the carriers. Commands are sent from the stoppers in order to move a carrier along the irradiation path or to stop its movement. Mathematical model based on state machine method is applied for simulating the carriers' movement along the irradiation path. Based on this mathematical model, an algorithm is made and its corresponding interactive computer program will be developed using the standard graphical interface  DESAIN PERANGKAT LUNAK DAN PEMODELAN SISTEM IRADIATOR SERBAGUNA Dilakukan desain perangkat lunak dan model simulasi sistem iradiator serbaguna. Sistem iradiator yang diteliti memiliki 19 carrier yang berjalan pada lintasan medan iradiasi di mana terdapat 9 stopper. Stopper ini berfungsi untuk mengendalikan gerakan seluruh carrier. Pada stopper terdapat mekamisme untuk memerintahkan carrier bergerak sepanjang segmen lintasan atau tetap diam. Metode state machine dipergunakan dalam pembuatan model matematis untuk menirukan mekanisme gerakan carrier pada lintasannya. Berdasarkan model ini maka akan dibangun algoritma dan kemudian perangkat lunak interaktif yang menggunakan antarmuka grafis